Cornel West and Prophetic Thought: Reflections on Community Within Community of Inquiry (Analytic Teaching, 1994)
Introduction: Much of the current research and writing on Community of Inquiry has focused on inquiry, specifically, it has focused on classroom discussion and how to move a classroom discussion in the direction of forming a community of inquiry. This is as it should be. Community of Inquiry, while finding its origins in Pierce's idea of a 19th century scientific community, has become focused and defined first in John Dewey and more recently and fully in Philosophy for Children (Lipman, Sharp, Onscanyan, 1980; Lipman, 1991) and in particular in the work of Ann Margaret Sharp (Sharp, 1985; Sharp, 1991). The current work by Laurance Splitter and Ann Sharp (in press) will provide an even more fully developed picture of community of inquiry within classroom practice and philosophy for children.